Analysis of Innovation Culture and Sound Governance in Mandiri VOE Program in Sibolahotang Village, Indonesia - Panjaitan, Debora S.; Frinaldi, Aldri (Al-Risalah, 2022)
This study aims to analyze the innovation culture of Village-Owned Enterprises (VOE) and the application of the sound governance dimension in developing programs for community welfare at Sibolahotang Sibulele Aritonang Sitampulak (SAS) Village. This was carried out using a qualitative descriptive method and the data were obtained through observation, interviews, and recording. Furthermore, the interview transcription data obtained from the field were analyzed using Manual Data Analysis Procedure (MDAP). The results showed the VOE innovation culture in Sibolahotang SAS Village has not been effective due to four challenges, namely weak Human Resources, the underdeveloped potential of the existing village assets, low financial resources, and the absence of cooperation with the private sector. The completion stage of these challenges entails conducting knowledge development training for Human Resources in savings and loan financial reporting for the Mandiri VOE program as well as collaborating with the private sector. Therefore, the village government is expected to provide facilities and infrastructure that can enhance the management of Mandiri VOE in order to run effectively and efficiently.